Angiotensin system inhibitors and survival in patients with metastatic renal cell carcinoma treated with VEGF‐targeted therapy: A pooled secondary analysis of clinical trials. Issue 9 (6th January 2016) - Sorich, Michael J.; Kichenadasse, Ganessan; Rowland, Andrew; Woodman, Richard J.; Mangoni, Arduino A.
Abstract : Use of angiotensin system inhibitors (ASIs; angiotensin receptor blockers or angiotensin‐converting enzyme inhibitors) has been reported to be associated with improved survival in metastatic renal cell carcinoma (mRCC), particularly when used with vascular endothelial growth factor‐targeted therapies. This study was a secondary pooled analysis of two Phase III randomized controlled trials (RCTs) of patients with mRCC: NCT00334282 comparing pazopanib to placebo and NCT00720941 comparing pazopanib to sunitinib. ASI users were defined as patients using an ASI at baseline. Association with overall survival (OS; primary outcome) and progression‐free survival (PFS) was evaluated using Cox proportional hazards regression. The association was adjusted in multivariable analysis for baseline systolic blood pressure (SBP), use of other antihypertensive drugs and prognostic factors comprising the Heng risk criteria for mRCC. Of 1, 545 patients pooled from the two RCTs, 649 (42%) were using one or more antihypertensive drugs at baseline, 385 (59%) of which were using an ASI. In the multivariable analysis of patients using pazopanib or sunitinib, no significant association was observed between baseline ASI use and OS (hazard ratio [HR] 0.97 [95% confidence interval (CI) 0.80–1.18], p  = 0.80) or PFS (HR 0.88 [95% CI 0.73–1.06], p  = 0.17). Exploratory subgroup analysis of NCT00720941 highlighted that the effect of baseline ASI use on OS may differ between patients treated with sunitinib and pazopanib. In conclusion, use of ASIs at baseline was not a significant independent prognostic factor for improved survival in a pooled analysis of mRCC patients treated with pazopanib or sunitinib. Abstract : What's new? Angiotensin system inhibitors (ASIs) have been reported to be associated with improved survival in metastatic renal cell carcinoma, particularly when used with vascular endothelial growth factor‐targeted therapies. In this secondary pooled analysis of two large clinical trials, the use of ASIs at baseline was, however, not found to significantly improve survival for patients with metastatic renal cell carcinoma treated with antiangiogenic therapy. Additionally, ASI use at baseline was not preferable to other antihypertensive drug classes in terms of survival. Exploratory analyses suggest that the effect of ASI may differ, depending on the specific antiangiogenic therapy and type of ASI used.